A question of priorities : democratic reforms and economic recovery in postwar Germany : Frankfurt, Munich, and Stuttgart under U.S. occupation, 1945-1949 /: democratic reforms and economic recovery in postwar Germany : Frankfurt, Munich, and Stuttgart under U.S. occupation, 1945-1949. (1996) - Unknown
No abstract available